The joy of falling : [large type] a novel - Harrel, Lindsay (Center Point Large Print, 2020)
"It has been fifteen months since Eva and Angela lost their thrill-seeking husbands in a scuba diving accident. Both women are trying to navigate their way through the grief, but neither one is making much progress. Angela is barely making ends meet, angry at her husband for leaving her to raise three children on her own. Meanwhile, Eva is stuck, unable to move forward after losing the love of her life and her source of inspiration. But then Eva gets a life-changing phone call. Before Brent and Wes died, they had signed up for a race of a lifetime-an ultra-marathon in beautiful New Zealand. Eva begs Angela to run the race with her in their husbands' place, and Angela finally agrees, hoping to finally understand her husband's choices. Training is exhausting, and the race is even more demanding. Their journey grows more complicated by the presence of two men-Marc is Brent's best friend who is running the race with Eva and Angela, and Simon King is a writer who is covering their inspiring story. With every step, Eva and Angela must ask themselves questions that they haven't had the courage to ask before. As the women literally put one foot in front of the other, they wonder: Is it possible to find their way forward in hope?"--Provided by publisher.